Analisa Hasil Pengelasan Oxi-Acetylene Dengan Kawat Las Tembaga dan Borak Pada Baja ST 37 - Saputra, Aldi Maulana; Choliq, Abdul (Jurnal Inovasi Ilmu Pengetahuan dan Teknologi (JIPTEK), 2024)
The use of bicycles in Indonesia has experienced significant growth as part of a lifestyle and sport. Bicycle frame materials have undergone several innovations from steel, aluminum, carbon fiber and even wood. Old bicycles have chromoly steel and high tensile steel frame materials. For reasons of convenience and hobby, many old bicycles are still cared for and used by bicycle hobbyists even though they need repair due to corrosion. Welding a frame with holes or breaks often becomes a problem, especially in determining the welding technique, type of welding and additional metal used. This research aims to determine the effect of mixing borax in welding additives on the tensile strength and hardness values ​​after welding using the oxy-acetylene method and copper and brass additives. The specimen is ST 37 steel, 200mm long, 20mm wide and 10mm thick. V-beam connection model with a 60⁰ angle. The resulting welds are tensile tested using the ASTM E-8 test standard. During the steel welding process, it was found that the additional metal in the form of copper without a mixture of borax was difficult to fuse with the base metal. However, if the copper is mixed with borax by dipping the copper tip before welding, it will be easier to fuse. The results of the hardness test showed that welded samples without borax had a lower tensile strength value compared to samples with metal added copper or brass with the addition of borax, namely 48.3 N/mm2 compared to 78.3 N/mm2. The hardness test results show that oxy-acetylene welding with added copper is 230HV, while welding with the addition of borax is lower, namely 160HV. Thus, it is concluded that for welding bicycle frames made of steel, it is best to use oxy-acetylene welding, because the fire produced is not too big and using additional copper or brass materials by adding borax to the additional metal.